Blueberry proanthocyanidins against human norovirus surrogates in model foods and under simulated gastric conditions. (May 2017) - Joshi, Snehal; Howell, Amy B.; D'Souza, Doris H.
Abstract: Blueberry proanthocyanidins (B-PAC) are known to decrease titers of human norovirus surrogates in vitro . The application of B-PAC as therapeutic or preventive options against foodborne viral illness needs to be determined using model foods and simulated gastric conditions in vitro . The objective of this study was to evaluate the antiviral effect of B-PAC in model foods (apple juice (AJ) and 2% reduced fat milk) and simulated gastrointestinal fluids against cultivable human norovirus surrogates (feline calicivirus; FCV-F9 and murine norovirus; MNV-1) over 24 h at 37 °C. Equal amounts of each virus (5 log PFU/ml) was mixed with B-PAC (1, 2 and 5 mg/ml) prepared either in AJ, or 2% milk, or simulated gastric fluids and incubated over 24 h at 37 °C. Controls included phosphate buffered saline, malic acid (pH 7.2), AJ, 2% milk or simulated gastric and intestinal fluids incubated with virus over 24 h at 37 °C. The tested viruses were reduced to undetectable levels within 15 min with B-PAC (1, 2 and 5 mg/ml) in AJ (pH 3.6). However, antiviral activity of B-PAC was reduced in milk. FCV-F9 was reduced by 0.4 and 1.09 log PFU/ml with 2 and 5 mg/ml B-PAC in milk, respectively and MNV-1 titers were reduced by 0.81 log PFU/ml with 5 mg/ml B-PAC in milk after 24 h. B-PAC at 5 mg/ml in simulated intestinal fluid reduced titers of the tested viruses to undetectable levels within 30 min. Overall, these results show the potential of B-PAC as preventive and therapeutic options for foodborne viral illnesses. Highlights: Blueberry proanthocyanidin (B-PAC) retained antiviral effect in apple juice. Anti-noroviral activity of B-PAC decreased in milk. B-PAC showed anti-noroviral activity under simulated gastric conditions.